Ballistic impact analysis of graphene nanosheets reinforced kevlar-29. (2021) - Vignesh, S.; Surendran, R.; Sekar, T.; Rajeswari, B.
Abstract: The bulletproof vests used by law enforcement officials can be appropriately termed as "Bullet-resistant" vests instead of bulletproof vests since they are not completely threat proof. The bullets released from handgun calibers such as 0.357 SIG or 9 mm guns travel at a very high velocity which the vests cannot withstand. These vests are mostly made of ceramic or steel plates backed with para-aramids such as kevlar, spectra, and dyneema. Kevlar is an organic fiber from an aromatic polyamide family. Kevlar has a unique molecular structure that distinguishes it from other polyamide families. The para-aramid structure gives kevlar an optimum combination of high tensile strength, high modulus, resilience, thermal stability, and toughness [1] . Different varieties of Kevlar are produced to be used in different applications. Kevlar-29 has been the most widely used material in bulletproof vests for ballistic protection. Despite its strength and resilience kevlar has its disadvantages such as poor compression strength, which makes it less reliable for ballistic protection. Although kevlar fibers are strong and have high tensile strength its ability to cope with the force of compression is poor [2] . Also, the inclusion of these plates significantly increases the weight of the jackets. Graphene, on the other hand, is a two-dimensional allotrope of carbon atoms arranged in a hexagonal lattice structure [3] . It is found to be the strongest material ever found yet weighs much less than a paper [4] . In this work, graphene nanoparticles are inserted as laminates in-between the kevlar fiber layers and dynamic ballistic impact analysis is done on this reinforced material. The equivalent stresses, total deformation, maximum principal stress and directional velocity of the vests and bullet are investigated and the results show a significant increase in the ballistic performance of vests reinforced with graphene laminates.